Effectiveness of revival assertiveness programs to increase assertiveness as an effort to address people pleasing behavior in High School Students - Hanna Maryama; Ulfah Sayidah Mutamimah; Juliana Nur Afifah; Fadhia Hasna Kamila; Krisbandaru Hayuningtyas; Siska Sugiharti (University of Merdeka Malang, 2025)
People-pleasing behavior can have negative impacts, particularly on adolescents, as it may hinder their ability to express personal opinions and needs openly. One approach to addressing this issue is by enhancing assertiveness. This study aims to examine the effectiveness of the Revival Assertiveness Programs as a medium to develop assertive communication in adolescents with people-pleasing tendencies. The study employed a quasi-experimental method using a one group pre-test post-test design within a within-subject framework. The population in this study consisted of students at SMA Negeri 1 Lembang. A total of 38 students were selected through purposive sampling based on the criteria of having high levels of people-pleasing and low levels of assertiveness. Data were collected using three standardized instruments: the Disease to Please Triangle Questionnaire, the Rathus Assertiveness Schedule (RAS), and the Inner Child Scale (ICS), all of which were adapted for the context of this research. Data analysis was conducted using normality testing and paired sample t-test. The results showed a significance value of p <.05, indicating that the Revival Assertiveness Programs had a significant effect on increasing assertive behavior and reducing people-pleasing tendencies. These findings suggest that the program is effective in fostering assertive communication among adolescent people-pleasers, particularly those influenced by wounded inner child experiences.